2012
DOI: 10.1155/2012/891318
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Cancer Imaging and Therapy

Abstract: Nanoparticle contrast agents offer the potential to significantly improve existing methods of cancer diagnosis and treatment. Advantages include biocompatibility, selective accumulation in tumor cells, and reduced toxicity. Considerable research is underway into the use of nanoparticles as enhancement agents for radiation therapy and photodynamic therapy, where they may be used to deliver treatment agents, produce localized enhancements in radiation dose and selectively target tumor cells for localized damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…Photoluminescent nanoparticles have been evaluated as contrast agents for the in vivo detection of tumors [115,116]. One of the first studies reported on in vivo cancer imaging using photoluminescent nanoparticles was published by Gao et al [117].…”
Section: Optical Imaging (Oi)mentioning
confidence: 99%
“…Photoluminescent nanoparticles have been evaluated as contrast agents for the in vivo detection of tumors [115,116]. One of the first studies reported on in vivo cancer imaging using photoluminescent nanoparticles was published by Gao et al [117].…”
Section: Optical Imaging (Oi)mentioning
confidence: 99%
“…These properties of the tumor cells together make the ERP effect that facilitate the accumulation of nanoparticles and thereinentrapped drug at higher concentration in the tumor site. nanoparticles have the potential to perform multiple functions in combination with PDT [317,325]. A polyacrylamide multifunctional platform with a contrast enhancer for magnetic resonance imaging (MRI), photosensitizer (Photofrin1) for PDT, PEG surface coating and targeting moiety (the integrin-targeting RGD peptide) was synthesized, and each functionalization aspect was demonstrated to be successful by Kopelman et al [326].…”
Section: Nanoparticles In Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…They are used to improve the enhancement of image contrast as compared to molecular species and improve the visibility of features that would otherwise be difficult to detect. They go on receiving considerable attention in this field for their potential as contrast agents, [2][3][4][5][6][7][8][9] offering many advantages compared to more conventional chemical agents such as greater biocompatibility and reduced toxicity [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%